Heraclius' Alleged Farewell Salute to Syria - Woods, David (Byzantion, 2018)
This paper offers a new explanation of the origin of the story as recorded by a variety of Syriac and Arabic sources that the emperor Heraclius had bade farewell to Syria as he retreated back to Constantinople in c. 637. It is argued that the Greek source at the root of this tradition had originally depicted Heraclius declaring 'Save (yourself), Syria!' to the inhabitants of northern Syria as he sought to evacuate them from the new border region, and not "Farewell, Syria!" to Syria itself. However, his language was ambiguous, and the initial Syriac translator misunderstood his intent.